THE EXPERIENCE OF SHADOW TEACHERS IN HELPING CHILDREN WTH SPECIAL NEEDS IN TELOGO PATUT ELEMENTARY SCHOOL I GRESIK - Abd Nasir; Indah Winarni; Retno Lestari (Journal of Nursing Science Update (JNSU), 2018)
Shadow teacher in their profession are always dealing with special needs children who have intellectual impairment, behavioral and emotional disorders and learning disorders. This is an exhausting job because shadow teachers should be able to ensure that the child is always adaptive during the lesson. Shadow teacher also must know how to adapt to the child’s character, and this task also spends a lot of time. However, the existence of children in the class is not supported by good learning guidelines. The purpose of this study was to explore the experience of shadow teachers with the child with special needed. This qualitative research used Interpretative phenomenology research design and data analysis used interpretative phenomenology analysis approach. Data collection process used in-depth interviews and observations, and this research involved six participants. This research produced 9 themes: (1) believe that this work is a blessing from Allah, (2) feel that there is a wisdom from helping each others (3) exhausting for mind and emotions, (4) feel not confident at the beginning of his profession, (5) havea feeling that this job is a meaningful job, (6) believe that the children can be disciplined with strict rules, (7) believe that visualization is the way to make children’s focus increased, (8) feel that togetherness must be build together with the children, and (9) feel that government and society’s concern to these children with special needs is still lacking. Guiding and leading children with special needs is hard to do, but if this job is done with a wholehearted feeling it can make an incredible effort and can make the children with special needs can live peacefully in the middle of society.Shadow teacher in their profession are always dealing with special needs children who have intellectualimpairment, behavioral and emotional disorders and learning disorders. This is an exhausting jobbecause shadow teachers should be able to ensure that the child is always adaptive during the lesson.Shadow teacher also must know how to adapt to the child’s character, and this task also spends a lotof time. However, the existence of children in the class is not supported by good learning guidelines.The purpose of this study was to explore the experience of shadow teachers with the child with specialneeded. This qualitative research used Interpretative phenomenology research design and data analysisused interpretative phenomenology analysis approach. Data collection process used in-depth interviewsand observations, and this research involved six participants. This research produced 9 themes: (1)believe that this work is a blessing from Allah, (2) feel that there is a wisdom from helping each others(3) exhausting for mind and emotions, (4) feel not confident at the beginning of his profession, (5) havea feeling that this job is a meaningful job, (6) believe that the children can be disciplined with strictrules, (7) believe that visualization is the way to make children’s focus increased, (8) feel thattogetherness must be build together with the children, and (9) feel that government and society’sconcern to these children with special needs is still lacking. Guiding and leading children with specialneeds is hard to do, but if this job is done with a wholehearted feeling it can make an incredible effortand can make the children with special needs can live peacefully in the middle of society.